Le rôle politique et stratégique de l’Arctique : une perspective norvégienne - Sollie, Finn (Études internationales, 1989)
Developments in many fields, and especially in technology and economies, in international politics and in military strategy, have combined to give the Arctic a more important role in international affairs. By geographical location, with its mainland and islands stretching far to the North and framing the maritime link between the Atlantic and the Arctic, Norway has a strategic position at the main gateway to and from the Arctic Basin. Historically, these European northern waters have been explored and exploited as an international commons and legally the Svalbard Treaty of 1920 which recognized Norway's sovereignty over the islands also secured permanent rights of access for foreign nationals and equal right to engage in research and to participate in commercial operations on the islands. In addition to the economic provisions, the Treaty served a strategic purpose by prohibiting the establishment of naval bases and fortifications on the islands and disallowing any use of them for « warlike purposes -». With the Soviet Union emerging as the major military power in Europe at the end of the Second World War and concentrating its new and global naval forces in northern bases on the Kola Peninsula, the northern waters between Norway's coasts have become a strategic core area for any contest for maritime control of Atlantic supply lines, as well as for the strategic nuclear balance between the two superpowers and for a new nuclear threat against Europe. In sum, the broad developments in the Arctic and the specific strategic interests in Arctic relations now focusing on the Norwegian Arctic, the Norwegian North has been turned into a center stage of international political and military interest and concern.